Learn to draw birds. - Partington, Peter (London : HarperCollins, 1998)
Provides easy-to-follow instructions for drawing differenttypes of birds.
Young Adult
Keywords: Birds in art; Drawing -- Technique; Birds in art; Drawing -- Technique